Citra Perempuan Salihah Dalam Akun Youtube Yufid.TV: Al-Qur’an, Hadis, Konstruksi, Dan Relevansi - Soleha, Sofiyatus; Miski (QOF, 2022)
Patriarchal culture is still developing in our society, where women are constructed as weak creatures and are behind men. This culture is inseparable from religious doctrines, which also lead to the discourse of restricting women’s movement; in this case, the labeling of salihah is a strong enough factor that women outside the home deviate from Islamic law. Yuvid.TV conveys one of the constructions that marginalize women on its YouTube channel. Therefore, the questionn answered in this study was how to construct salihah women through Yufid.TV's interpretation of QS. An-Nisā’[4]: 34 considering that Yufid.TV in several of its shows also discussed salihah women. Then this study examined how relevant this interpretation to the contemporary context. By using Karl Mannheim's sociology of knowledge approach and descriptive-critical analysis, this study showed that Yufid.TV's understanding in interpreting QS. An-Nisā’[4]: 34 tends to be textual and seems indifferent to the social conditions of the surrounding community. So that this pious construction reflects on the patriarchal mindset, namely the effort to make women as secondary beings whose duties are limited to domestic affairs only. In fact, in the contemporary social context, the discourse of women's equality has been widely expressed. Where many women have succeeded in proving that their existence is worthy of consideration